Efficient production of levulinic acid using metal-organic framework catalyst: Role of brønsted acid and flexibility - LEEBOWOO; Jin Young Seo; Jeong, Keunhong; Choi, Jungkyu; Yong Cho, Kie; Cho, Sangho; Baek, Kyung-Youl (Elsevier BV, 2022)
Alternative commodity production utilizing biomass has attracted significant interest in recent decades. The conversion of glucose into valuable products has been highly researched owing to its abundance, price competitiveness, and carbon-neutral cycle. In this study, various types of Bronsted acid groups, according to their pKa values and specific alkyl spacers, were impregnated into UiO-66, and the catalytic activity for levulinic acid (LA) production from glucose was investigated. Moreover, by controlling the reaction temperature, we demonstrated that the UiO-66-NH-R-SO3H catalyst with the strongest Bronsted acid and desired alkyl spacer can produce LA in a 71.6% yield. To the best of our knowledge, the effect of an alkyl spacer and a Bronsted acid group using MOF was first discovered for biomass conversion.